WEB-BASED VOCABULARY MATERIAL: NEED ANALISYS AT ENGLISH EDUCATION DEPARTMENT OF UIN ALAUDDIN MAKASSAR - Sitti Nurpahmi; Aslindah Syam; Subaedah Subaedah; Kamsinah Kamsinah; Kartini Lammase; Ulfiatul Tizam (International Conference on Social and Islamic Studies, 2021)
This study aims to utilize the impact of internet technology and learning sources by investigating students' need concerning web-based vocabulary material. Need analysis is the starting point in material dvelopment. The research design used by the researcher is survey research. The research subject is the first-year students of English education department at UIN Alauddin Makassar consisting of 100 participants. The instruments of the research are questionnaire, interview.The students' need analysis of web-based preposition learning material consisted of four aspects. The first is an introduction. The second is linguistics' need. Then, the third is learning's need. The last is the display setting. The result of data shows that the students need to improve their vocabulary as requirements to finish the study. There is no exercises or training to practice the vocabularies. So that it needs to design and develop vocabulary materials that fulfil the students’ need. The students need to put all aspect of vocabulary in material: definition, function, form, and type. In material design, it needs to stress on proper place of the vocabularies, because students are difficult to put a proper place of vocabularies. It should also put pictures and animation, exercises, and vocabulary list. The also should be colorful. It should put some material by using visual, audio, and kinesthetic.